Slack resources and export intensity: New empirical evidence from Vietnam - Thi Thanh Binh Dinh; Tu Thuy Anh; Thi Mai Phuong Chu (Economies, 2023)
The paper explored the effects of financial and human resource slacks on firms' export intensity. Using longitudinal data of Vietnamese firms with a random effect model, the study found that financial slack had an inverted-U shaped effect; meanwhile, human resource slack had no consistently significant effect on firms' export intensity. The empirical findings could have managerial practice implications at the firm level. Too few - or too many - slack resources are bad for export intensity. Therefore, firm managers need to consider the necessary level of redundancy for slack resources to avoid prodigality while doing business. This study contributed new insights to international business and slack literatures. First, our findings contributed to the international business literature. In classic internalization studies, it has generally been believed that firms with access to greater resources are more likely to exploit foreign markets. However, our research showed that, when there were too many slack resources, business activities in firms' foreign markets, such as exports, could be reduced due to complacency among firm managers. Second, the research results contributed to literature on slack resources, providing a new insight on their effects on firms' export intensity. Aside from linear or U-shaped effects, slack resources could have inverse U-shaped relationships with firms' export intensity.
Keywords: 330; export intensity; financial slack; human resource slack; slack resources